Did Burns send Cannon to France in 1792? – A New Theory of the Narrative. Issue 2 (September 2022) - Carruthers, Gerard; McLean, Ralph
Abstract : The story of Burns sending carronades to revolutionary France in 1792 first appears in the biography by John Gibson Lockhart (1828). An analysis of the extant evidence, including documents in the National Library of Scotland, suggests the unlikelihood of the narrative and it may be that its origins lie in the real-life events surrounding Professor John Anderson (1726–96) who did take ordnance to France in 1791.